Properties of Paraspinal Muscles in Japanese High School Baseball Players With Terminal‐Stage Lumbar Spondylolysis. Issue 2 (30th June 2017) - Tsuboi, Hiroyuki; Nishimura, Yukihide; Sakata, Takeshi; Tanina, Hideaki; Arakawa, Hideki; Nakamura, Takeshi; Umezu, Yuichi; Tajima, Fumihiro
Abstract: Background: Lumbar spondylolysis is a defect in the pars interarticularis that is common in young athletes; the stress distribution at the pars interarticularis is the highest in extension and rotation movements. The paraspinal muscles play an important role in stabilization of the lumbar spine; however, no study has assessed the properties of paraspinal muscles in athletes with lumbar spondylolysis. Objective: To evaluate the properties of paraspinal muscles in athletes with lumbar spondylolysis. Design: Cross‐sectional study. Setting: Laboratory. Participants: Six high school baseball players with terminal‐stage lumbar spondylolysis and 11 high school baseball players without organic lumbar lesions of similar anthropometric characteristics. Methods: All subjects performed the unsupported trunk holding test combined with surface electromyographic (EMG) power spectral analysis until exhaustion. The results of EMG power spectral analysis were compared between the spondylolysis and control groups. Main Outcome Measurements: The median frequency (MF) was computed from the raw EMG signal of the erector spinae and multifidus during trunk holding test using fast Fourier transform spectrum analysis. The initial MF and MF slope were calculated. Results: No significant differences in endurance time were found between the spondylolysis and control groups. The initial MF and the MF slopes of the erector spinae and multifidus were significantly lower in the spondylolysis group than in the control group. Conclusions: The results suggest lower fast‐twitch motor unit recruitment in the erector spinae and multifidus of high school baseball players with terminal‐stage lumbar spondylolysis compared with the control. Level of Evidence: IV